Sri Lanka : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper explores how monetary policy affects other macroeconomic variables, mainly output and inflation. First, it provides an overview of the framework for implementing monetary policy and then discusses the transmission mechanism itself. In this study, the following statistical data are listed in detail: GDP and expenditure components, savings, investment, current account, consumption and prices of petroleum and electricity, price indicators, employment by economic sectors, monetary survey, selected interest rates, balance of payments, exports and imports by commodity, direction of trade, services and income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet